Effect of Aging on Fatty Streak Formation in a Diet-Induced Mouse Model of Atherosclerosis - Li, Yuhua (2007)
Age is considered to be a major risk factor for atherosclerosis, but it is unclear whether age has a direct effect on susceptibility to atherosclerosis. Wild-type mice develop fatty streak lesions in the aortic root only when fed a cholate-containing high fat/cholesterol diet. To investigate the influence of age on fatty streak formation, young (10 weeks) and old (53 weeks) female C57BL/6 mice were fed an atherogenic diet containing 15% fat, 1.25% cholesterol and 0.5% sodium cholate for 12 weeks. Atherosclerotic lesions at the aortic root were measured after cryosections were stained with oil red O. Results showed that old mice developed a comparable size of aortic lesions with young counterparts (5,600 ± 2,480 vs. 6,457 ± 1,537 μm(2)/section; p = 0.77), although old mice had significantly higher plasma cholesterol levels than young mice on the atherogenic diet (p < 0.05). Plasma levels of soluble vascular cell adhesion molecule 1 were significantly higher in old mice than in young mice on both chow and Western diets (p < 0.005). These data indicate that age has no direct effect on atherosclerosis susceptibility although it is accompanied by elevations in plasma cholesterol and vascular cell adhesion molecule 1 levels in C57BL/6 mice. Thus, increased cardiovascular events with age are probably related to a progressive increase in plaque size rather than to an increase in atherosclerosis susceptibility.